Novel Perfused Compression Bioreactor System as an in vitro Model to Investigate Fracture Healing - Hoffmann, Waldemar; Feliciano, Sandra; Martin, Ivan; de Wild, Michael; Wendt, David (Frontiers in Bioengineering and Biotechnology, 2015)
Secondary bone fracture healing is a physiological process that leads to functional tissue regeneration via endochondral bone formation. In vivo studies have demonstrated that early mobilization and the application of mechanical loads enhances the process of fracture healing. However, the influence of specific mechanical stimuli and particular effects during specific phases of fracture healing remain to be elucidated. In this work, we have developed and provided proof-of-concept of an in vitro human organotypic model of physiological loading of a cartilage callus, based on a novel perfused compression bioreactor system (PCB). We then used the fracture callus model to investigate the regulatory role of dynamic mechanical loading. Our findings provide a proof-of-principle that dynamic mechanical loading applied by the PCB can enhance the maturation process of mesenchymal stromal cells towards late hypertrophic chondrocytes and the mineralization of the deposited extracellular matrix. The PCB provides a promising tool to study fracture healing and for the in vitro assessment of alternative fracture treatments based on engineered tissue grafts or pharmaceutical compounds, allowing for the reduction of animal experiments.